Is the Machecoul fault the source of the ∼M6 1799 Vendée earthquake (France)?. Issue 3 (25th February 2021) - Kaub, C; Geoffroy, L; Bollinger, L; Perrot, J; Le Roy, P; Authemayou, C
SUMMARY: The ∼ M 6 1799 Bouin earthquake is considered as one of the largest earthquakes to have struck Western France. However, the seismogenic source potentially responsible for this event remain marginally documented. We present results from a focused offshore-onshore multidisciplinary survey in its meizoseismal area in order to identify the fault segments that potentially ruptured during this earthquake. Based on macroseismic data and the geology, we focused our study on the so-called Machecoul Fault as a potential source of the 1799 Bouin event. Our survey includes extensive high-resolution seismic reflection, high resolution bathymetry and a 1-yr seismological survey. These data were combined with existing topography, onshore gravity data and drill data to document the geometry of the Marais Breton/Baie de Bourgneuf basin, the past tectonic activity and the current local microearthquakes at depth along its bounding faults. Offshore and onshore observations suggest a recent activity of the segmented Machecoul Fault bounding the basin to the North. Offshore, the planar contact between the Plio-Quaternary sediments and the basement along the fault trace as well as the thickening of these sedimentary units near this contact suggests tectonic control rather than erosion. Onshore, the recent incision of the footwall of the fault suggests a recent tectonic activity. The temporary local seismological experiment deployed between 2016 and 2017 recorded a diffuse microseismicity down to the depth of 22 ± 5 km along the southward dipping Machecoul Fault, associated with predominantly normal fault mechanisms. Altogether, these results suggest that the Machecoul Fault is a serious candidate for being the source of the historical Bouin 1799 earthquake.